Two-year mortality and end-of-life decisions after traumatic spinal cord injury: data from a Level 1 Trauma centre in the Netherlands - Menco J.S. Niemeyer; Felix Peuker; Said Sadiqi; Monika C. Kerckhoffs; R. Marijn Houwert; Karlijn J.P. van Wessem; Marcel W.M. Post; Janneke M. Stolwijk (Medical Journals Sweden, 2023)
Objective: Literature shows high in-hospital mortality rates following end-of-life decisions in patients with traumatic spinal cord injury. This study investigated 2-year mortality and end-of-life decisions in patients with traumatic spinal cord injury. Design: Explorative retrospective study in a Dutch level 1 trauma centre. Patients: All consecutive patients between 2015 and 2020 with new traumatic spinal cord injury were selected from the trauma registry. Patients were excluded if myelopathy, cauda equina, or conus medullaris injury was absent or if they were referred to another level 1 trauma centre. Methods: Mortality and end-of-life decisions (i.e. withdrawal and withholding of treatment, and euthanasia) within 2 years were analysed. Demographics, injury and clinical characteristics, and hospital treatment outcomes were compared with survivors. Motivations and critical morbidities concerning end-of-life decisions were assessed. Results: The sample included 219 patients. Two-year mortality was 26% (n = 56), in-hospital mortality was 16%. The deceased were older, had more comorbidities and more severe injuries. end-of-life decisions concerned 42 patients (75%), mostly motivated by loss of independence or poor outcomes. Three patients received euthanasia (5%). The largest group with end-of-life decisions also sustained moderate-severe traumatic brain injuries (n = 11; 26%). Conclusion: Most patients with traumatic spinal cord injury died following an end-of-life decision, with the largest group sustaining concomitant traumatic brain injuries. The incidence of euthanasia was low.